Systematic Literature Review : Penerapan Teori Antrian dalam Optimasi Sistem Pelayanan - Asrah Nabila Purba; Fadhilah Rahmah; Mukhlida Khofipah; Wahyu Wahono; Siti Salamah Br Ginting (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Queuing theory is a quantitative approach widely used to analyze and optimize service systems. This study aims to systematically examine the application of queuing theory in various service sectors based on previous research. The method used is a Systematic Literature Review (SLR) by examining a number of relevant scientific articles published between 2020 and 2025. The analysis process is carried out through the stages of identification, selection, and synthesis of literature, with a focus on the types of queuing models and their areas of application. The results of the study indicate that the Single Channel–Single Phase (M/M/1) and Multi Channel–Single Phase (M/M/s) models are the most dominant models used in the banking, healthcare, retail, transportation, and public service sectors. The application of queuing theory has been proven to reduce waiting times, increase operational efficiency, and improve service quality. This study is expected to serve as a reference for service managers and future researchers in designing more optimal service systems.